Upaya Meningkatkan Hasil Belajar Elemen Digital Marketing dengan Media Interaktif Classpoint - Dewi, Liska Citra Kurnia; Patrikha, Finisica Dwijayati; Kurniati, Lilik (STKIP PGRI SITUBONDO, 2024)
This research aims to enhance the understanding and learning outcomes of 12th-grade students in the Digital Business program at SMK Negeri 1 Surabaya, specifically in the Digital Marketing concentration, which is often complex and abstract. Digital Marketing materials require a dynamic and interactive learning approach to accommodate the predominantly visual learning styles of the students. Interactive media, specifically Classpoint, was selected as a solution to present the material in a more engaging and visual manner. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. The first cycle faced challenges such as low student engagement due to unfamiliarity with the interactive media and technical issues. However, after improvements were made in the second cycle through training and selecting more suitable features, there was a significant increase in student engagement and learning outcomes. The average post-test score improved from 85 in the first cycle to 90 in the second cycle, with a percentage increase of 31%. The findings suggest that the use of Classpoint interactive media can significantly enhance students' understanding and learning outcomes in Digital Marketing.